Multitemporality and Diversity in the Reading Processes of Condiciones Extremas - Acuña-Zumbado, Eduardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
“Condiciones Extremas” (1998, 2000, 2005) by Colombian Juan B. Gutiérrez, is a hypernovel which by its temporal narrative structure manipulates the dispersion of its subject-reader and characters within the general textual strategies of a science fiction novel, where the temporal element is essential in the interpretation of this digital narrative. “Condiciones Extremas” uses “Literatronic” as an artificial intelligent engine which creates a unique narrative for each subject-reader according to the reading choices each reader selects by interacting with this engine. ”Literatronic” hinders the reader from feeling completely lost while attempting to read this hypertext.